Hydrocracking optimization of palm oil to bio-gasoline and bio-aviation fuels using molybdenum nitride-bentonite catalyst - Hasanudin, Hasanudin; Asri, Wan Ryan; Said, Muhammad; Hidayati, Putri Tamara; Purwaningrum, Widia; Novia, Novia; Wijaya, Karna (the Royal Society of Chemistry, 2022)
In this study, molybdenum nitride-bentonite was successfully employed for the reaction of hydrocracking of palm oil to produce a bio-gasoline and bio-aviation fuel. The prepared catalyst was characterized using XRD, FT-IR, and SEM-EDX. The acidity of the catalyst was determined using the pyridine gravimetric method. The result showed that the acidity of bentonite was increased after modification using molybdenum nitride. The hydrocracking study showed that the highest conversion and product fraction of bio-gasoline and bio-aviation fuel were exhibited by molybdenum nitride-bentonite 8 mEq g−1. The catalyst was later used to optimize the hydrocracking process using RSM-CCD. The effects of the process variables such as temperature, contact time, and catalyst to feed ratio, on the response variables, such as conversion, oil, gas, and coke yield, were investigated. The analysis of variance showed that the proposed quadratic model was statistically significant with adequate precision to estimate the responses. The optimum conditions in the hydrocracking process were achieved at a temperature of 731.94 K, contact time of 0.12 h, and a catalyst to feed ratio of 0.12 w/v with a conversion of 78.33%, an oil yield of 50.32%, gas yield of 44.00% and coke yield of 5.73%. The RSM-CCD was demonstrated as a suitable method for estimating the hydrocracking process of palm oil using a MoN-bentonite catalyst due to its closeness to the optimal value of the expected yield. This study provided a potential catalyst of based on bentonite modified using molybdenum nitride for the hydrocracking of palm oil.